PENGARUH STRESS KERJA TERHADAP TURNOVER INTENTIONS PADA ERA DIGITALISASI PERBANKAN - Dinda Zanubba Faruq; Dr. Sri Suwarsi, S.E., M.Si., CGA (UNISBA Press, 2022)
Abstract. Digitalization is the main factor that causes very high work stress and has an influence on the increase in Turnover Intention. This study aims to determine and analyze 1) To analyze employee work stress in the era of digitalization of banking at Bank Rakyat Indonesia KCP Tasikmalaya. 2) To analyze Employee Turnover Intentions in the banking digitalization era at Bank Rakyat Indonesia KCP Tasikmalaya. 3) To analyze the influence of work stress on Employee Turnover Intentions of banking digitalization at Bank Rakyat Indonesia KCP Tasikmalaya. The research method used is descriptive and verification analysis and operates the calculations using the SPSS 26.0 program. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The number of the population is relatively small or the study wants to make generalizations with very small errors. Another term for saturated sample is census, where all members of the population are sampled. The sample is 67 employees of BRI KCP Tasikmalaya. The results of this study conclude that 1) Work Stress is with the largest score of 288, while the dimension that produces the lowest score is with a score of 286. Work Stress Variable produces an average value of 287 and is on the continuum line of 82.0% thus The statement of Job Stress is included in the “Very High” category. 2) Turnover Intention, which is with the largest score of 297, while the dimension that produces the lowest score is with a score of 286. The Turnover Intention variable produces an average value of 292 and is on the continuum line of 84%, thus the statement from Turnover Intention belongs to the category